Studi Eksperimental Pengaruh Ketinggian dan Sudut Kemiringan Modul Fotovoltaik Terapung terhadap Perilaku dan Potensi Degradasi Termal pada Panel Surya - Muhammad Reza Fathoni; Bambang Arip Dwiyantoro (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Floating Photovoltaic (FPV) systems enhance performance through the natural cooling effect of water bodies, yet module operating temperature remains a critical factor affecting electrical performance and long-term reliability and is strongly influenced by physical configuration. This study analyzes the effects of module height above the water surface (250, 500, and 750 mm) and tilt angle (5°, 15°, and 25°) on photovoltaic cell temperature (Tmod) and the Arrhenius Acceleration Factor (AF) as an indicator of thermal degradation potential. Measurements were conducted on an FPV system at ITS Graha Pond, Surabaya, Indonesia, from 09:00 to 15:00 local time at 30-minute intervals, analyzed using the Taguchi L9(3²) Orthogonal Array, Signal-to-Noise (S/N) ratio, Main Effect Analysis (MEA), and Analysis of Variance (ANOVA). Results show Tmod ranged from 32.91°C to 54.96°C, yielding AF values between 3.9488 and 5.9110. The optimal configuration (A₃B₃: 750 mm height, 25° tilt) produced Tmod = 48.10°C and AF = 4.0524. ANOVA identified module height as the most dominant factor, contributing 72.92% to Tmod variation and 68.93% to AF variation, statistically significant at α = 0.05. Tilt angle contributed 13.82% (Tmod) and 16.25% (AF) but was not significant. These findings underscore the importance of selecting appropriate FPV physical configurations to reduce operating temperature, enhance energy efficiency, and extend system service life in tropical climates.